Efektivitas Pemberian Audiovisual Tentang Bantuan Hidup Dasar (BHD) Terhadap Tingkat Pengetahuan Nelayan Dalam Menangani Korban Tenggelam - Khairin Wanda Aurelia; Adiratna Sekar Siwi; Made Suandika (Ilmiah Institut Citra Internasional, 2023)
Cases of drowning in the sea which are quite high require first treatment, which is mostly done by fishermen. The handling cannot be separated from the provision of Basic Life Support (BLS) to drowning victims by fishermen, so fishermen must have basic knowledge of how to provide Basic Life Support (BLS). The aimed of the study was to determine the effectiveness of providing audiovisuals about Basic Life Support on the level of knowledge of fishermen in dealing with drowning victims in Jetis Village. The research design was two group pre-post test design. 140 respondents was invited to this study. The research instrument used a knowledge questionnaire and audiovisual media. Data analysis using wilcoxon test. The results showed that fishermen before the intervention had an average score of 14.47 in the control group and 13.84 in the experimental group and after the intervention had an average value of 14.39 in the control group and 15.77 in the experimental group. The results of the Wilcoxon test showed a p-value of 0.000 (p-value ). The conclusion is that there was an effect of providing audiovisuals about BLS on the knowledge of fishermen in dealing with drowning victims in Jetis Village.